Ungkapan Fatis Pada Dialog Dalam Buku Koala Kumal Karya Raditya Dika - Prapti Wigati Purwaningrum (Wanastra: Jurnal Bahasa dan Sastra, 2018)
The purposes of the analysis are to find the phatics categories and the function of it in the context of the dialog. The writer provides data  from the dialog which consist of phatic categories then analyze it. The data of the analysis are taken from Koala Kumal book written by Raditya Dika. Phatic chategories by Kridalaksana, the function of language by Leech, Criteria of phatics by Jacobson are choosen as the theory in this analysis. Based on the analysis the writer found some categories and the function of phatics. Particle as the phatic category which is mostly found in Koala Kumal book. It has the function to convince the meaning of the statement. Phrases and words are also found in it such as terima kasih, apa kabar, assalamualaikum, wassalamualaikum, and halo. The function of  Assalamualaikum, halo, apa kabar are to start the conversation. Besides that terima kasih and wassalamualakum as phrase annd words category of fatis are also used to end the conversation.   Key Word: speech situation, phatic categories, Koala Kumal Book Written By Raditya Dika